An Internet-Based Asthma Self-Management Program Increases Knowledge About Asthma: Results of a Randomized Controlled Trial - Kohler, Benedikt (Dtsch Arztebl Int, 2020)
BACKGROUND: Asthma education (AE) is associated with reduced hospitalization and disability. We compared the effectiveness of an electronic AE program (eAEP) with a conventional face-to-face AE program (presence-based AEP; pAEP) for asthma knowledge (AK) with regard to self-management. METHODS: A randomized controlled pilot study was conducted in a pulmonary rehabilitation clinic. AK was determined by means of the Asthma Knowledge Test (AKT). The change in AKT score within each group was calculated with a paired t-test. Group differences were estimated with adjusted linear regression models. RESULTS: In the intervention group (n = 41), the AKT score increased from 41.57 (standard deviation 5.63) at baseline to 45.82 (3.84) after completion of the eAEP (p < 0.001), and again to 47.20 (3.78) after completion of the pAEP (p = 0.046). In the control group (n = 41), the score increased from 41.73 (4.74) at baseline to 45.72 (3.65) after completion of the pAEP (p < 0.001). There was no relevant difference in knowledge gain between the eAEP and the pAEP group after completion of the corresponding educational sessions (p = 0.881). The AKT score was higher in the eAEP group after obligatory participation in pAEP than in the group that only completed the pAEP (p = 0.020). CONCLUSIONS: An internet-based AEP could help to reduce the knowledge deficits of a large proportion of patients with asthma.